2002
DOI: 10.1063/1.1426245
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial SnO2 thin films grown on (1̄012) sapphire by femtosecond pulsed laser deposition

Abstract: An ultrafast (100 fs) Ti sapphire laser (780 nm) was used for the deposition of SnO2 thin films. The laser-induced plasma generated from the SnO2 target was characterized by optical emission spectroscopy and electrostatic energy analysis. It was found that the ionic versus excited-neutral component ratio in the plasma plume depends strongly on the amount of background oxygen introduced to the deposition chamber. Epitaxial SnO2 films with high quality and a very smooth surface were deposited on the (1̄012) sapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
65
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 23 publications
5
65
0
Order By: Relevance
“…XRD pole figures ͑not shown here͒ indicate that the film is single crystalline and is epitaxially grown with its ͓010͔ axis along the ͓1210͔ direction of the Al 2 O 3 substrate, consistent with the previous report in Ref. 16. The dependence of the ͑101͒ plane spacing, d 101 , on the V concentration is shown in Fig.…”
Section: Sample Preparation and Characterizationsupporting
confidence: 77%
“…XRD pole figures ͑not shown here͒ indicate that the film is single crystalline and is epitaxially grown with its ͓010͔ axis along the ͓1210͔ direction of the Al 2 O 3 substrate, consistent with the previous report in Ref. 16. The dependence of the ͑101͒ plane spacing, d 101 , on the V concentration is shown in Fig.…”
Section: Sample Preparation and Characterizationsupporting
confidence: 77%
“…The XRD patterns indicate that both of the fi lms are of rutile structure; the fi lm grown on the Si substrate is polycrystalline with random orientation, while the fi lm grown on the Al 2 O 3 substrate has (101) orientation. Pole fi gure results (not shown) further revealed that the fi lm grown on Al 2 O 3 is single crystal and is epitaxially grown with its [010] axis along the [1¯210] direction of the Al 2 O 3 substrate, consistent with the result in [12]. The (101) plane spacing of the fi lms grown on Al 2 O 3 decreases almost linearly as the V concentration increases, suggesting that at least some V goes into the SnO 2 lattice and substitutes for Sn.…”
supporting
confidence: 77%
“…[6][7][8][9][10][11][12][13][14][15] In spite of this effort, however, very little has been done on the nature and properties of the material obtained from this ablation process once it is deposited on a substrate surface, either in the form of a continuous film or as nanoparticles. Deposition of continuous thin films using fs lasers has been successful in the case of oxides or nitrides, [16][17][18][19][20][21] with ablation in the presence of a gas in the deposition chamber that reacts or interacts to some extent with the ejected material, leading to the growth of a continuous film on the substrate.…”
Section: Introductionmentioning
confidence: 99%